Who's a major? A novel approach to peer group selection ; empirical evidence from oil and gas companies - Frank Asche; Bård Misund (Cogent Economics & Finance, 2016)
This study presents a novel approach to selecting comparable companies in equity valuation. While valuation multiples is probably the most common valuation method in practice, discounted cash flow and residual income valuation models are advocated by academics. A key aspect in valuation by multiples is peer group selection. In this paper, we examine the usefulness of econometric techniques in peer-group selection for the largest companies in the international oil and gas sector. Using Chow tests, we are able to identify firms with similar relationships between valuation multiples and relevant value drivers. These results of our study suggest that analysts and investors should, when carrying out valuations, be careful in selecting the companies that comprise the peer groups. Comparable company selection could be carried out using econometric techniques that select companies on the basis of similarities in the relation between financial information and market valuation, instead of being based purely on analysts' subjective judgments.
Keywords: 330; oil and gas companies; oil majors; valuation; valuation multiples; peer groups; p/e; Exxon